Molecular simulation of confined fluids in carbon nanotubes - Teo, Min Lun. (2010)
Carbon nanotubes (CNTs) have many significant and potential applications, in which many of them involve confined fluid in equilibrium. Therefore, we used molecular simulations to study in depth the behavior of the confined fluid particles in CNTs, especially in the area of their phase equilibrium behavior. The characteristics of CNTs are defined by the rolling orientation of the graphite sheet which is defined by a large number of indices, (n,m). In this project, our main focus will be the metallic CNTs which is represented by n – m divisible by 3. Well known potential interactions like Brenner and Lennard-Jones are utilized to describe the fluid-CNT and carbon-carbon interactions. Properties of equations of states involving the confined fluid and carbon, first-order phase transition, density distribution and bond order parameters results are collected to allow us to study the behavior of confined fluid in CNTs in greater details.